Estudo numérico do gerenciamento térmico de um motor de combustão interna com foco na maximização do desempenho veicular - Fabrício Thomaz (2020)
Nowadays, fuel consumption improvements and reduction of pollutant emissions are being much discussed. Downsizing and downspeeding are among the many methods widely applied to increase the overall energy efficiency of vehicles equipped with internal combustion engines. In high engine loads, engine coolant temperature and air charge temperature (ACT) values can be so high that they compromise overall system performance. In this case, a strategy of power derate calibration is used to increase the system reliability. The management of the engine speed could be enable to control the ACT through engine load decrease by engine speed increase, however, at the same time, could be impact the coolant temperature due effects on engine heat rejection. Thus, the current work aims to analyze, through numerical models, cooling system design strategies focus on maintenance of the generated power, at high torque and ambient temperature conditions, managing engine load and speed. Then, according cooling module configurations strategies, perform an assessment of fuel consumption under FTP-75 + HWFET cycle. Through engine load and speed management, the results showed the possibility of to mitigate up to 30% of engine power derate, at extreme vehicle driving conditions. For lower fuel consumption, it is preferable to increase the cooling fan power combined with smaller radiators, showing gains up to 0.8%. The results suggest that to avoid a little power derate at extreme load conditions, the required effort is too high, penalizing the fuel consumption under FTP-75 + HWFET cycle. From these results, the proposal is, to develop a suitable engine derate calibration, searching to minimize the performance losses at high engine loads, and then, minimize the fuel consumption at normal vehicle driving conditions.